2017
DOI: 10.1159/000485535
|View full text |Cite
|
Sign up to set email alerts
|

Isogambogenic Acid Inhibits the Growth of Glioma Through Activation of the AMPK-mTOR Pathway

Abstract: Background/Aims: Glioma is the most devastating cancer in the brain and has a poor prognosis in adults. Therefore, there is a critical need for novel therapeutic strategies for the management of glioma patients. Isogambogenic acid, an active compound extracted from the Chinese herb Garcinia hanburyi, induces autophagic cell death. Methods: Cell viability was detected with MTT assays. Cell proliferation was assessed using the colony formation assay. Morphological changes associated with autophagy and apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…5C). The results obtained when the cells were treated with compound C (10 µmol/L for 2 h), which is an AMPK inhibitor, were similar to those obtained with the cells transfected with AMPK-siRNA [30, 31], with decreases in ATG5 expression and LC3-II transformation (Fig. 5D).…”
Section: Resultssupporting
confidence: 77%
“…5C). The results obtained when the cells were treated with compound C (10 µmol/L for 2 h), which is an AMPK inhibitor, were similar to those obtained with the cells transfected with AMPK-siRNA [30, 31], with decreases in ATG5 expression and LC3-II transformation (Fig. 5D).…”
Section: Resultssupporting
confidence: 77%
“…The serine/threonine kinase mechanistic target of rapamycin (mTOR) functions as a mediator of cell survival, which is believed to be oncogenic [ 23 ]. The activation of AMPK might have a negative regulatory effect on mTOR expression, which is known to be resistant to apoptosis by regulating the activation of the caspase cascade and autophagy [ 24 , 25 ]. The results of this study showed that baicalin activated the SIRT1 / AMPK signaling, which further inhibited the phosphorylation of mTOR, resulting in an increase in apoptosis of human NSCLC cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of α-, β-, and γ-subunits [23,24]. Phosphorylation of the α1-subunit at Thr-172 is essential for AMPK activation [23][24][25]. Activated AMPK is shown to promote cell survival under stress conditions [26].…”
Section: Introductionmentioning
confidence: 99%